Africa, Asia, and the history of philosophy : racism in the formation of the philosophical canon, 1780-1830 - Park, Peter K. J. (SUNY series, philosophy and race., 2013)
A historical investigation of the exclusion of Africa and Asia from modern histories of philosophy.